Mathematical Model of Transmission Network Static State Estimation - Ivanov, Aleksandar S; Đorđević, Dragan (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
In this paper the characteristics and capabilities of the power transmission network static state estimator are presented. The solving process of the mathematical model containing the measurement errors and their processing is developed. To evaluate difference between the general model of state estimation and the fast decoupled state estimation model, the both models are applied to an example, and so derived results are compared.